Hubungan antara OHIS dengan Kebutuhan Perawatan Periodontal Pasien Skizofrenia di RS Jiwa - Dirman, Rezki; Asnuddin, Asnuddin; Sakinah, Sri; Laiya, Nova; Zulkaidah, Utari (TIN: Terapan Informatika Nusantara, 2025)
It is important to prioritize oral health as an important component of overall medical care. Patients with mental illnesses are particularly susceptible to oral diseases, especially when hospitalized. Factors such as the type of psychiatric illness, length of treatment, and side effects of treatment can affect their oral health. Additionally, behaviors associated with mental illness, such as alcoholism, drug abuse, and smoking, can further exacerbate oral health problems in this population. The purpose of the study was to determine the relationship between oral hygiene and periodontal care needs in schizophrenia patients in the male inpatient room of the Prof. DR. V.L Ratumbuysang Mental Hospital, North Sulawesi Province. This type of research uses an analytical observational design with a cross-sectional approach. This research was conducted in the male inpatient room of RSJ Prof. Dr. V.L. Ratumbuysang in June-July 2024. The study population was all male schizophrenia patients who were treated in the inpatient room of Prof. Dr. V.L. Ratumbuysang Hospital which amounted to 85 patients. Samples were taken using the Total Sampling Technique with the criteria that the patient was calm and cooperative when the examination was carried out. It was found that 60 samples met the inclusion and exclusion criteria. Then the results of the study found a relationship between oral hygiene and the need for periodontal care of schizophrenia patients in the male inpatient room of Prof. Dr. V. L. Ratumbuysang Manado Hospital. The correlation coefficient value obtained was 0.896, meaning that the hygiene strength of the oral cavity and the need for periodontal care of schizophrenia patients were strong.